Use of Protective Gloves in Nail Salons in Manhattan, New York City - Corey Basch; Christina Yarborough; Stephanie Trusty; Charles Basch (Korean Society for Preventive Medicine, 2016)
Objectives: Nail salon owners in New York City (NYC) are required to provide their workers with gloves and it is their responsibility to maintain healthy, safe working spaces for their employees. The purpose of this study was to determine the frequency with which nail salon workers wear protective gloves. Methods: A Freedom of Information Law request was submitted to New York Department of State's Division of Licensing Services for a full list of nail salons in Manhattan, NYC. A sample population of 800 nail salons was identified and a simple random sample (without replacement) of 30% (n=240) was selected using a random number generator. Researchers visited each nail salon from October to December of 2015, posing as a potential customer to determine if nail salon workers were wearing gloves. Results: Among the 169 salons in which one or more workers was observed providing services, a total of 562 workers were observed. For 149 salons, in which one or more worker was observed providing services, none of the workers were wearing gloves. In contrast, in six of the salons observed, in which one or more workers was providing services, all of the workers (1 in 2 sites, 2 in 1 site, 3 in 2 sites, and 4 in 1 site) were wearing gloves. Almost three-quarters of the total number of workers observed (n=415, 73.8%) were not wearing gloves. Conclusions: The findings of this study indicate that, despite recent media attention and legislation, the majority of nail salon workers we observed were not wearing protective gloves when providing services.